Teledermatology protocol for screening of Skin Cancer - Maria Fernanda Piccoli; Bruna Dücker Bastos Amorim; Harley Miguel Wagner; Daniel Holthausen Nunes (Sociedade Brasileira de Dermatologia, 2015)
BACKGROUND: Telemedicine refers to the use of technology as improvement of healthcare delivery to places where distance becomes an obstacle. Its use represents a great potential for dermatology, a specialty whose visual analysis phase is essential in diagnosis. OBJECTIVES: To analyze the compatibility index of skin cancer diagnoses between primary care and teledermatology, and to validate a protocol for standardization of digital imaging to obtain the reports in teledermatology. METHODS: An observational cross-sectional study developed through the census of 333 examination requests, received between January/2012 and July/2012, in the Center for Telemedicine and Telehealth of SES-SC. We used a protocol for photographic lesion standardization, consisting of three steps (panoramic photo, close-up with ruler and dermoscopy). After collection, the data were sent to a virtual site on the Internet, and recorded with the use of an electronic health record containing the images, the skin phototype and demographic characteristics. RESULTS: The level of compatibility between the diagnosis of skin cancer in Santa Catarina's primary care and the diagnosis proposed by teledermatology was 19.02%. Proportionally, it was 21.21% for BCC, 44.44% for SCC and 6.98% for MM. The protocol was statistically significant (p <0.05), with an OR of 38.77. CONCLUSION: The rate of diagnostic compatibility of skin cancer was low and the use of the protocol optimized the chance of validating requests for examination.